2022
DOI: 10.1371/journal.pone.0270758
|View full text |Cite
|
Sign up to set email alerts
|

Community-based health insurance, healthcare service utilization and associated factors in South Gondar Zone Northwest, Ethiopia, 2021: A comparative cross-sectional study

Abstract: Introduction Community-based health insurance schemes are becoming increasingly recognized as a potential strategy to achieve universal health coverage in developing countries. Ethiopia has implemented community-based health insurance in piloted regions of the country. The scheme aims to improve the utilization of healthcare services by removing financial barriers. There is a dearth of literature regarding the effect of the insurance scheme on the utilization of healthcare services. Methods A community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The probability of using health services was 8 times among family with chronic disease among insured HHs compared with 4.9 times in NI HHs than their counterparts. Studies done in Kenya 33 and the South Gondar Zone Northwest, Ethiopia, 30 the South Gondar Zone 34 and Chilga District, 35 support this study’s findings. This could be due to the presence of adverse selection, in which the higher the presence of chronic disease, the higher the chance of being insured in CBHI.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The probability of using health services was 8 times among family with chronic disease among insured HHs compared with 4.9 times in NI HHs than their counterparts. Studies done in Kenya 33 and the South Gondar Zone Northwest, Ethiopia, 30 the South Gondar Zone 34 and Chilga District, 35 support this study’s findings. This could be due to the presence of adverse selection, in which the higher the presence of chronic disease, the higher the chance of being insured in CBHI.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, a study conducted in the South Gondar Zone found that health insurance enrolment significantly increased HSU, with 67.8% and 33.7% of family members visiting health institutions within 3 months among CBHI users and non-users, respectively. 30 The disparity could be attributed to a difference in the time period considered, as this study only looked at 6 months of healthcare utilisation. Also, there may be differences in the perspectives measured, indicating that this study focused on HSU in general, whereas others focused on outpatient services and relied on pilot studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 . This is because the Ethiopian government approved and initiated the CBHI practice in the Tigray and Amhara regions before rolling it out nationwide to improve healthcare quality [ 49 ]. As a result, the prevalence of CBHI in Ethiopia differs from region to region, with higher enrollment rates in the Amhara and Tigray regions than in others [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, children under five have been chosen based on their gender (male and female) and age (below one year, 1–2 years, and 4–5 years). On the other hand, the auxiliary variables of the parents included sex (male and female), place of residence (urban and rural), age (15–24, 25–34, 35–44, and 45–49), source of drinking water (improved and unimproved), educational levels (non-educated, elementary, secondary, and above), literacy (literate and illiterate), marital status (married, never married, and others), type of toilet facility (has toilet facility and does not have toilet facility), the number of sons who passed away (none, one, or two or more), the number of daughters who passed away (none, one, or two or more), the size of the family (less than five, and five or more), the presence or absence of disabilities (disabled and not), and the type of employment (government employment, private employment, self-employment, employer, unemployed, or other employment) [ 2 , 48 , 49 ]. These variables are considered at the zonal level as auxiliary variables in SAEs.…”
Section: Methodsmentioning
confidence: 99%